(1)-12/3*(-7)-12/4*(-7)+12/5*7 (2)(-10^2)+[-4^2-(1-2^3)*2]
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 00:36:36
(1)-12/3*(-7)-12/4*(-7)+12/5*7(2)(-10^2)+[-4^2-(1-2^3)*2](1)-12/3*(-7)-12/4*(-7)+12/5*7(2)(-10^2)+[-
(1)-12/3*(-7)-12/4*(-7)+12/5*7 (2)(-10^2)+[-4^2-(1-2^3)*2]
(1)-12/3*(-7)-12/4*(-7)+12/5*7
(2)(-10^2)+[-4^2-(1-2^3)*2]
(1)-12/3*(-7)-12/4*(-7)+12/5*7 (2)(-10^2)+[-4^2-(1-2^3)*2]
(1)-12/3*(-7)-12/4*(-7)+12/5*7
=7*(12/3+12/4+12/5)
=7*1
=7
(2)(-10^2)+[-4^2-(1-2^3)*2]
=-100+[-16-(-7)*2]
=-100-16+14
=-116+14
=-102
(1)-12/3*(-7)-12/4*(-7)+12/5*7
=7*(12/3+12/4+12/5)
=7*1
=7
(2)(-10^2)+[-4^2-(1-2^3)*2]
=-100+[-16-(-7)*2]
=-100-16+14
=-116+14
=-102
知道了把
(1)7*(4+3+2.4)=7*9.4=65.8
(2)100+(16+10)=126
1,4,3,8,5,12,7,( ).( )里应填几
1/36÷(-1/4-5/3+7/12)
4×(-15)×(-7/8+1又3/4)-7/12) 4×(-15)×(-7/8+1又3/4)-7/12) 简便计算~
找规律,1 3 2 6 4( ) ( ) 12 7
12/7÷(2/3-1/4) 要简算
1,4,3,8,5,12,7,()
(1又3/4-7/8-7/12)除以(-7/8)+(-2/3)
(1又3/4-7/8-7/12)/(-7/8)+(-8/3)
(1又3/4+7/8-7/12)×(-1又1/7)
(1)-12/3*(-7)-12/4*(-7)+12/5*7 (2)(-10^2)+[-4^2-(1-2^3)*2]
(1又3/4+7/8-7/12)*(1又1/7)是加!
(-15)/(1/3-3/2-3)x6(-7/8)/(7/4-7/8-7/12)
习题3,4,7,12,(),28
1-12分之7+4分之3
1+3/4-7/12等于多少
2、4、4、12、8、36、( )、( )1、3、4、7、11、18、( )、( )
计算(能简算的要简算) 15/16-(2/3+1/4) 1/4-7/12+3/4-5/12
(1又3/4减7/8减7/12)÷(-7/8)加(-7/8)÷(1又3/4减7/8减1/12) 要(1又3/4减7/8减7/12)÷(-7/8)加(-7/8)÷(1又3/4减7/8减1/12)